Systematic Literature Review: Penerimaan Pengguna Terhadap Aplikasi Fintech Berdasarkan Model UTAUT2 - Muhammad Rafi Irsyadhie; Arista Pratama; Siti Mukaromah (Universitas Multi Data Palembang, 2026)
The rapid development of fintech has increased the importance of understanding user acceptance of fintech applications. This study aims to analyze user acceptance of fintech applications using a Systematic Literature Review approach. The review focuses on the application of the UTAUT2 model as a framework for explaining technology acceptance and factors influencing the adoption of fintech applications. This study examines scientific articles published between 2020 and 2025 that are relevant to the topic of fintech user acceptance. The findings indicate that UTAUT2 variables such as performance expectancy, effort expectancy, and facilitating conditions are frequently used to explain user acceptance. In addition, several studies incorporate external variables to address fintech characteristics, such as trust and perceived risk. This study also provides a comprehensive overview of significant variables and research trends related to fintech applications.